Research on Application of Network Coding in Hybrid Mesh ALM Model - Lian He; Chanle Wu; Jun Yue; Shi Cheng; Gang Ye (2009 International Conference on Multimedia Information Networking and Security, 2009)
In the study of ALM, how to improve the performance of multicast system is a hotspot. Theoretical study shows that network coding can improve the performance of network multicast. In this paper, in accordance with the actual structure and features of HM-ALM, a cluster-oriented, and hybrid mesh ALM model, we select the deterministic linear coding strategy, and design the appropriate coding algorithm. The experimental results show that, using network coding in ALM system with hybrid mesh model can reduce transmission delay and enhance the system robustness with a certain amount of link redundancy.